2012
DOI: 10.1111/j.1365-2966.2012.21828.x
|View full text |Cite
|
Sign up to set email alerts
|

AzTEC half square degree survey of the SHADES fields - II. Identifications, redshifts and evidence for large-scale structure

Abstract: The Astronomical Thermal Emission Camera (AzTEC) 1.1 mm survey of the two SCUBA HAlf Degree Extragalactic Survey (SHADES) fields is the largest (0.7 deg2) blank‐field millimetre‐wavelength (mm‐wavelength) survey undertaken to date at a resolution of ≃18 arcsec and a depth of ≃1 mJy. We have used the deep optical to radio multiwavelength data in the SHADES Lockman Hole East and SXDF/UDS fields to obtain galaxy identifications for ≃64 per cent (≃80 per cent including tentative identifications) of the 148 AzTEC‐S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 151 publications
(280 reference statements)
2
32
1
Order By: Relevance
“…We find that for the bright population the distribution of p-values is similar to that obtained if we perform the same operation with 50 random samplings of the parent field, though with a slightly more significant low p-value tail. Approximately 10 per cent of the field pairs exhibit p < 0.05, suggesting that it is not necessarily as uncommon as one would expect by chance to find that redshift distributions derived from non-contiguous pencil beams of sky fail the KS test, as in Michałowski et al (2012). For the faint population, 92 per cent of the field pairs have p < 0.05.…”
Section: Redshift Distributionmentioning
confidence: 94%
See 1 more Smart Citation
“…We find that for the bright population the distribution of p-values is similar to that obtained if we perform the same operation with 50 random samplings of the parent field, though with a slightly more significant low p-value tail. Approximately 10 per cent of the field pairs exhibit p < 0.05, suggesting that it is not necessarily as uncommon as one would expect by chance to find that redshift distributions derived from non-contiguous pencil beams of sky fail the KS test, as in Michałowski et al (2012). For the faint population, 92 per cent of the field pairs have p < 0.05.…”
Section: Redshift Distributionmentioning
confidence: 94%
“…In particular, Michałowski et al (2012) found evidence that photometric redshift distributions of radio-identified counterparts of 1100 and 850 µm selected SMGs in the two non-contiguous SCUBA Half-Degree Extragalactic Survey (SHADES) fields are inconsistent with being drawn from the same parent distribution. This suggests that the SMGs are tracing different large-scale structures in the two fields.…”
Section: Simulated Observations Of Smgs 1785mentioning
confidence: 99%
“…For the machine-learning analysis, we note that previous work has shown that SMGs are in general at high redshift, are relatively bright in the rest-frame near-infrared, and have red colors in the optical and near-infrared wavebands (e.g., Smail et al 2002;Chapman et al 2005;Hainline et al 2009;Michałowski et al 2012;Wang et al 2012;Alberts et al 2013;Simpson et al 2014;. To compare the properties of the SMGs to the field, we use as our ("non-SMG") control sample those K-band-detected sources that are located within the primary beams of our ALMA maps but are >1 6 away from an ALMA-identified SMG.…”
Section: Method: Radio + Machine-learning Identificationsmentioning
confidence: 99%
“…We will focus on the radio and redder optical and near-infrared bands, as the dusty, starforming SMGs are expected to be typically brighter in these wavebands than the bulk of the field population (e.g., Wardlow et al 2011;Michałowski et al 2012;Hodge et al 2013;Simpson et al 2014). …”
Section: Multiwavelength Observationsmentioning
confidence: 99%
See 1 more Smart Citation